2020
DOI: 10.1042/bsr20201232
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory effect of has-circ-0001146/miR-26a-5p/MNAT1 network on the proliferation and invasion of osteosarcoma

Abstract: Osteosarcoma is a malignant bone tumour with the lowest survival rates out of all paediatric cancers and is primarily diagnosed in children and adolescents. MNAT1 is a subunit in the cyclin-dependent kinase-activating kinase complex. Abnormal up-regulation of MNAT1 has been associated with the poor prognosis of multiple cancers. Bioinformatics analysis showed that has-circ-0001146 and miR-26a-5p were involved in the regulation of MNAT1 in osteosarcoma. The present study investigated the regulatory effects of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Circ_0102049, for example, promotes OS progression via modulating miR-1304-5p/MDM2 axis [ 8 ]. Circ_0001146 represses miR-26a-5p expression and up-regulates MNAT1 expression in OS cells, hence impeding OS growth [ 9 ]. Reportedly, circ_0081001 expression is elevated in OS tissues, cell lines, as well as patients' serum; COX regression analysis indicates that circ_0081001 is an independent risk factor that predicts the poor prognosis of the patients with OS [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Circ_0102049, for example, promotes OS progression via modulating miR-1304-5p/MDM2 axis [ 8 ]. Circ_0001146 represses miR-26a-5p expression and up-regulates MNAT1 expression in OS cells, hence impeding OS growth [ 9 ]. Reportedly, circ_0081001 expression is elevated in OS tissues, cell lines, as well as patients' serum; COX regression analysis indicates that circ_0081001 is an independent risk factor that predicts the poor prognosis of the patients with OS [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, by further analyzing of AlkAniline-Seq dates and validation studies, we revealed that METTL1 de ciency dramatically reduces the mature of miR-26a-5p via m 7 G methylation, which has been reported to act as a tumor suppressor in osteosarcoma 38,39 . METTL1-mediated m 7 G position has been identi ed to be essential for let-7e stem-loop equilibrium and thereby promotes its processing, which can further selectively regulate the translation of oncogenic mRNAs in hepatoma carcinoma cells 10 .…”
Section: Discussionmentioning
confidence: 86%
“…Circular RNAs have also been linked to a higher incidence of metastases, particularly in the lungs, as reported in the literature. C39 [ 48 ], C43 [ 49 ], and C36 [ 50 ] are some examples. Moreover, circRNAs have been associated with advanced Enneking/TNM stages of osteosarcoma, as it was seen with C51 [ 51 ], C17 [ 52 ], and C60 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%